A Rigorous Derivation and Validation of Two-Port Admittance and Impedance Parameters for the Exact Equivalent Circuit of a Single-Phase Power Transformer - Sadek M. F. Elkurie; Hassan Alghamoudi; Naji Gajam; Islam Ali Esmail (Journal of Scientific and Human Dimensions, 2026)
The imperative for computational efficiency in large-scale power system analyses, such as load-flow and fault studies, necessitates compact yet precise models for network components. While the classical exact T-equivalent circuit of a single-phase transformer offers the highest fidelity in characterizing operational behavior, its structural complexity often demands simplification for real-time simulation and large-network integration. This paper presents a comprehensive mathematical framework for deriving the exact two-port impedance